Wild Seaweed at Kerandangan Senggigi Beach, Batu Layar District, West Lombok Regency - Nunik Cokrowati; Nur Yatin; Jayusri Jayusri; Irika Devi Anggraini (Jurnal Natur Indonesia, 2024)
Seaweed algae is a type of marine plant classified as benthic macroalgae and mostly lives on the bottom of the water. Algae are seaweeds that live in the sea and belong to the thallophyta group. Seaweed contains many nutrients such as carbohydrates, vitamins, fats, minerals, and others that have great potential for development in various industries. As a maritime country, Indonesia has potential coastal and marine natural resources that can be utilized to improve the welfare of coastal communities. Seaweed is one of the many coastal and marine natural resources found along the coast of the Indonesian oceans. West Nusa Tenggara (NTB) is one of the seaweed-producing areas. One of the areas that can be seen is seaweed, especially wild seaweed, in the Senggigi area, Batu Layar District, West Lombok, precisely on Kerandangan Beach. This study aimed to analyze the types of seaweed and the phytochemical content of seaweed growing on Kerandangan Beach, Senggigi, West Lombok. This study uses the purposive sampling method by taking samples that are considered representative of the research location, which is done by taking samples randomly based on the boundaries of the area that has been determined. The results of this study are There are several types of seaweed in Kerandangan Beach Borgesenia forbesii, Corallina, Gelidium, Caulerpa taxifolia, Padina, Chondrus crispus, Sargassum cristaefolium, Galaxaura rugosa, Acanthopora spicifera, Ulva intestinalis, Halimeda opuntia, and Turbinaria decurrens. This research concludes that the type with the highest antioxidant content is Padina sp., which is 81.31% and has a chlorophyll content of 14.39 mg/L.